On the ecological context of the earliest human settlements in Europe: Resource availability and competition intensity in the carnivore guild of Barranco León-D and Fuente Nueva-3 (Orce, Baza Basin, SE Spain). (1st July 2016) - Rodríguez-Gómez, Guillermo; Palmqvist, Paul; Rodríguez, Jesús; Mateos, Ana; Martín-González, Jesús A.; Espigares, M. Patrocinio; Ros-Montoya, Sergio; Martínez-Navarro, Bienvenido
Abstract: With an age of ∼1.4 Ma, the Early Pleistocene archaeopaleontological sites of Barranco León and Fuente Nueva-3 (Orce, Baza Basin, SE Spain) provide the oldest evidence on human presence in Western Europe, including the finding of a deciduous tooth of Homo sp., huge lithic assemblages of Oldowan tradition and abundant cut-marks on large mammal bones. Here we use a mathematical approach based on Leslie matrices to quantify for the large mammal species preserved at the sites the biomass of primary consumers available, the distribution of meat resources among the secondary consumers and the competition intensity within the carnivore guild. The results obtained show a community of large mammals with a high diversity of secondary consumers that would satisfy slightly less than half of their dietary requirements under optimal ecological conditions. In the case of Homo sp., and considering that flesh resources were obtained through the scavenging of ungulate carcasses, the model indicates that the ecosystems of the basin could hold 10–14 individuals per 100 km 2 during a year, a value that is close to the mean population density of recent hunter-gatherers. These density estimates decrease slightly when a mixed hunting-scavenging strategy is considered and even more in the case of a strict hunting behavior. In addition, the value of the species competition index obtained for Homo sp. is among the lowest of the carnivore guild. These results suggest that the hominin populations that inhabited Southeast Spain during the Early Pleistocene behaved more as opportunistic scavengers than as active predators. Highlights: BL-D and FN-3 record the first human presence in the Early Pleistocene of Europe. Resource distribution and competition intensity in the carnivore guild are estimated. The ecosystems of the basin could hold 10–14 individuals of Homo sp. per 100 km 2 . These hominins behaved more as opportunistic scavengers than as active predators.